European Stroke Organisation (ESO) guidelines on management of transient ischaemic attack. (June 2021) - Fonseca, Ana Catarina; Merwick, Áine; Dennis, Martin; Ferrari, Julia; Ferro, José M; Kelly, Peter; Lal, Avtar; Ois, Angel; Olivot, Jean Marc; Purroy, Francisco
The aim of the present European Stroke Organisation Transient Ischaemic Attack (TIA) management guideline document is to provide clinically useful evidence-based recommendations on approaches to triage, investigation and secondary prevention, particularly in the acute phase following TIA. The guidelines were prepared following the Standard Operational Procedure for a European Stroke Organisation guideline document and according to GRADE methodology. As a basic principle, we defined TIA clinically and pragmatically for generalisability as transient neurological symptoms, likely to be due to focal cerebral or ocular ischaemia, which last less than 24 hours. High risk TIA was defined based on clinical features in patients seen early after their event or having other features suggesting a high early risk of stroke (e.g. ABCD2 score of 4 or greater, or weakness or speech disturbance for greater than five minutes, or recurrent events, or significant ipsilateral large artery disease e.g. carotid stenosis, intracranial stenosis). Overall, we strongly recommend using dual antiplatelet treatment with clopidogrel and aspirin short term, in high-risk non-cardioembolic TIA patients, with an ABCD2 score of 4 or greater, as defined in randomised controlled trials (RCTs). We further recommend specialist review within 24 hours after the onset of TIA symptoms. We suggest review in a specialist TIA clinic rather than conventional outpatients, if managed in an outpatient setting. We make a recommendation to use either MRA or CTA in TIA patients for additional confirmation of large artery stenosis of 50% or greater, in order to guide further management, such as clarifying degree of carotid stenosis detected with carotid duplex ultrasound. We make a recommendation against using prediction tools (eg ABCD2 score) alone to identify high risk patients or to make triage and treatment decisions in suspected TIA patients as due to limited sensitivity of the scores, those with score value of 3 or less may include significant numbers of individual patients at risk of recurrent stroke, who require early assessment and treatment. These recommendations aim to emphasise the importance of prompt acute assessment and relevant secondary prevention. There are no data from randomised controlled trials on prediction tool use and optimal imaging strategies in suspected TIA.